1990
DOI: 10.1111/j.1751-1097.1990.tb01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Time Resolved Spectroscopic Studies on the Intact Human Lens

Abstract: The human lens is continually under photooxidative stress from ambient radiation. In the young lens the major absorbing (between 300-400 nm) species is the glucoside of 3-hydroxy kynurenine. Using time resolved fluorescence spectroscopy on both the isolated compound and the intact human lens, the first excited singlet state of this compound is shown to have fast (ps) decay processes. This would tend to minimize damage to lens constituents because there would be little time for energy transfer into more harmful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 17 publications
0
67
0
Order By: Relevance
“…Kynurenines are weak photosensitizers and redirect the absorbed light energy into benign channels. [4][5][6][7] They are characterized by a low fluorescence quantum yield and lifetime, 4 a low triplet yield, 8 a high photochemical stability, 9,10 and, under aerobic conditions, a low singlet oxygen and/or superoxide photogeneration. 6 All these observations point to the existence of a fast S 1 f S 0 radiationless deactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Kynurenines are weak photosensitizers and redirect the absorbed light energy into benign channels. [4][5][6][7] They are characterized by a low fluorescence quantum yield and lifetime, 4 a low triplet yield, 8 a high photochemical stability, 9,10 and, under aerobic conditions, a low singlet oxygen and/or superoxide photogeneration. 6 All these observations point to the existence of a fast S 1 f S 0 radiationless deactivation.…”
Section: Introductionmentioning
confidence: 99%
“…These changes would reduce the amount of light input to the circadian clock located in the suprachiasmatic nuclei (SCN) of the hypothalamus. Within the crystalline lens accumulation of high molecular weight crystallin aggregates (Jedziniak et al, 1973;Yu et al, 1985) and yellow chromophores (Dillon and Atherton, 1990) cause an increase in light scattering and light absorption, respectively. As a result the density of the lens increases with ageing (Weale, 1954;Coren and Girgus, 1972;Xu et al, 1997) causing an alteration in the spectral absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The rise in absorption is highest for wavelengths at the blue end of the spectrum, around 460–470 nm, and, as noted, this has been attributed to the postnatal accumulation of yellow chromophores [116]. Mellerio [117]found that the optical density of the lens at 400 nm was about equal in the cortex and nucleus of the young lens, but became higher in the nucleus in the older lens.…”
Section: Scatter Absorption and Fluorescencementioning
confidence: 99%